Conocimientos, actitudes y prácticas de los principios bioéticos del profesional de enfermería en el cuidado del paciente hospitalizado, del Hospital II De Vitarte-EsSalud, 2011 - Barrenechea Baca, Liria Oportuna (2019)
The objective of the research was to determine the level of knowledge, attitudes and practices of bioethical principles of nursing in inpatient care, the Hospital II-EsSalud Vitarte, 2011. Design Studio quantitative, exploratory anddescriptive scope. Was conducted in a sample composed of 35 nurses who work in nursing care Medical Services,Surgery, Emergency and ICU (Intensive Care Unit). A questionnaire was used to measure the level of knowledge,attitudes and a scale for a guide to practical observation. Areas covered in this study were: Ethics, Ethics, Bioethics,beneficence, autonomy, confidentiality, informed consent, justice. The results were that 20% of participants havean excellent level of knowledge of bioethical principles, 45.7% have a good level, 31.4% and 2.9% regularly has apoor level. Regarding attitude levels of bioethical principles is positive 71.4% and 28.6% has a moderately positiveattitude level. As for practices, 60% of participants practiced bioethical principles during patient care. Which meansthat most nurses, have a level of knowledge and level of attitudes of bioethical principles, good and positive respectively. Similarly, the level of practice is acceptable and required in patient care.